Analysis of the Role of the Creative Economy in Advancing Product Business at MTs Al-Jauhariyah - Rohim, Abd (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
This study aims to analyze the role of the creative economy to improve product business in MTs Al-Jauhariyah. In addition to being an educational center, secondary schools also have the potential as a locus of local economic development through creative products. The creative economy is the main focus to increase competitiveness and economic contribution from product businesses in the school environment. Using qualitative research methods, data were collected through in-depth interviews with related parties, direct observation, and documentation studies. The results showed that creativity, innovation, and invention play a key role in the development of product business in this school. In terms of product concept, innovation and differentiation through the creative economy provide significant added value. Factors such as local community involvement, utilization of local resources, and integration of curriculum with creative economy aspects also strengthen the positive impact on the development of product business at MTs Al-Jauhariyah. This research contributes to the practical and theoretical understanding of how the creative economy can be implemented in secondary education environments, exactly in MTs Al-Jauhariyah. This finding can be a foundation for policy makers, schools, and education practitioners to optimize the role of the creative economy in developing product businesses in similar institutions. In addition, this research also opens opportunities for further research related to the integration of creative economy concepts in the context of formal education.